Development and Validation of a Novel Nomogram for Predicting Tumor-Distant-Metastasis in Patients with Early T1-2 Stage Lung Adenocarcinoma - Gu W (Dove Medical Press, 2020)
WeiGuo Gu,1,2 MingBin Hu,1,2 WeiJia Wang,1 Chao Shi,3 JinHong Mei1 1Department of Pathology, The First Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, People’s Republic of China; 2First Clinical Medical College, Nanchang University, Nanchang, Jiangxi, People’s Republic of China; 3Department of Oncology, The First Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, People’s Republic of ChinaCorrespondence: JinHong MeiDepartment of Pathology, The First Affiliated Hospital of Nanchang University, No. 17 Yong Wai Street, Nanchang, Jiangxi 330006, People’s Republic of ChinaEmail mjhdoctor@126.comChao ShiDepartment of Oncology, The First Affiliated Hospital of Nanchang University, No. 17 Yong Wai Street, Nanchang, Jiangxi 330006, People’s Republic of ChinaEmail 43286143@qq.comBackground: Distant metastasis in early T1-2 (diameter≤ 5 cm) stage lung adenocarcinoma (ET-LUAD) patients largely affect treatment strategies in clinical practice. However, the associated mechanism remains unclear and related studies is less. This study aimed to establish and validate a novel nomogram to predict the risk of distant metastasis in ET-LUAD.Methods: A total of 258 patients diagnosed with ET-LUAD and not receiving any treatment were recruited into this study. The patients were randomly divided into a training cohort and validation cohort in a ratio of 1:2. Univariate and multivariate logistic regression analysis was used to select the most significant predictive risk factors associated with distant metastasis in the training cohort. The established nomogram was validated by the consistency index (C-index), calibration curve, and decision curve analysis (DCA).Results: There were 124 patients with confirmed distant metastasis and 134 patients with non-distant metastases ET-LUAD were enrolled in the study. Multivariate logistic hazards regression analysis identified independent risk factors associated with distant metastasis to include platelet-to-lymphocyte ratios (PLR), lactate dehydrogenase (LDH), neural-specific enolase (NSE), carcinoembryonic antigen (CEA) and cytokeratin 19 fragments (Cyfra211), which were included in the establishment of the nomogram. The nomogram achieved a high consistency (C-index=0.792), good calibration, and high clinical application value in the validation cohort.Conclusion: The established nomogram can be used to predict distant metastasis in high-risk ET-LUAD nonmetastasis patients and can also be used by doctors to guide preventive and individualized treatment for ET-LUAD patients.Keywords: lung adenocarcinoma, distant metastasis, nomogram